An automatic drug injection device with spatial micro-force perception guided by an microscopic image for robot-assisted ophthalmic surgery - Li, Zhen; Fu, Pan; Wei, Bing-Ting; Wang, Jie; Li, An-Long; Li, Ming-Jun; Bian, Gui-Bin (Frontiers in Robotics and AI, 2022)
Retinal vein injection guided by microscopic image is an innovative procedure for treating retinal vein occlusion. However, the retina organization is complex, fine, and weak, and the operation scale and force are small. Surgeons’ limited operation and force-sensing accuracy make it difficult to perform precise and stable drug injection operations on the retina in a magnified field of image vision. In this paper, a 3-DOF automatic drug injection mechanism was designed for microscopic image guiding robot-assisted needle delivery and automatic drug injection. Additionally, the robot-assisted real-time three-dimensional micro-force-sensing method for retinal vein injection was proposed. Based on the layout of three FBG sensors on the hollow outer wall of the nested needle tube in a circular array of nickel-titanium alloys, the real-time sensing of the contact force between the intraoperative instrument and the blood vessel was realized. The experimental data of 15 groups of porcine eyeball retinal veins with diameters of 100–200 μm showed that the piercing force of surgical instruments and blood vessels is 5.95∼12.97 mN, with an average value of 9.98 mN. Furthermore, 20 groups of experimental measurements on chicken embryo blood vessels with diameters of 150–500 μm showed that the piercing force was 4.02∼23.4 mN, with an average value of 12.05 mN.